Estimates of HIV incidence among drug users in St. Petersburg, Russia: continued growth of a rapidly expanding epidemic. - Niccolai, Linda M; Verevochkin, Sergei V; Toussova, Olga V; White, Edward; Barbour, Russell; Kozlov, Andrei P; Heimer, Robert (European journal of public health, 2011)
Russia has one of the world's fastest growing HIV epidemics and it has been largely concentrated among injection drug users (IDU). St Petersburg, Russia's second largest city, is one of the country's regions that has been most affected by the HIV epidemic. To monitor the current epidemic situation, we sought to estimate recent HIV incidence among IDU in St Petersburg.
Keywords: Adolescent; Adult; Behavior, Addictive; Cohort Studies; Cross-Sectional Studies; Demography; Female; HIV; HIV Infections; Humans; Immunoenzyme Techniques; Incidence; Male; Middle Aged; Retrospective Studies; Russia; Socioeconomic Factors; Substance Abuse, Intravenous; Urban Population; Young Adult